Towards facilities management practice within a different environment - Mala Ali Modu; Maimunah Sapri; Zafirah Abd Muin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This paper examines facilities management practice within a different environment. It assessed how the facilities manager responds differently in a different environment. Therefore, an extensive review of documented literature related to the concept of FM and the role of the facilities manager was conducted which forms part of the methodology. The review revealed that FM entails an integrated approach to maintaining, improving, and adapting the buildings, systems, and services of an organization to create an environment that strongly supports the primary objectives of that organization. The facility manager or the FM practitioner is therefore responsible for the effective and efficient provision of facilities and services to support an organization in achieving its primary objectives through operational and strategic approaches. The provision of these services follows the specific needs and requirements of the organization regardless of the application of generic standard solutions and practices or a universal approach. The paper suggests that the facilities manager or practitioner respond differently in a different environment rather than confining to generic standards and best practices. This is because appropriate FM practice and arrangement for a given organization determines by factors such as the organization's characteristics, facility features, business sector, and environmental factors.